Significance of Vivianite Precipitation on the Mobility of Iron in Anaerobically Digested Sludge - Roussel, Jimmy; Carliell-Marquet, Cynthia (Frontiers in Environmental Science, 2016)
Anaerobic digestion requires a balanced availability of micro-nutrients with ideal growth conditions to reach optimal organic degradation and biogas production. Iron is the most abundant of the essential metals in an anaerobic digester and its mobility has a strong impact on microorganisms through its own bioavailability, but also through its influence on the bioavailability of other metals. Most previous research on iron mobility in anaerobic digestion has focused on sulfide as the controlling anion because digesters traditionally are sulfide rich and phosphate poor. However, chemical phosphorus removal (CPR) at wastewater treatment works (WWTW) can elevate phosphate concentrations in the digester 10-fold or more. The goal of this research was hence to examine the accepted wisdom of iron-sulfide dominance prevailing in all anaerobic digesters and by evaluating the potential for iron phosphate formation in municipal digesters treating CPR sludge. To fulfil this aim, iron compounds were identified experimentally from full-scale digesters at WWTW with CPR and the most likely iron species identified through modelling according to their thermodynamic probability of formation under the specific environmental conditions experienced in each anaerobic digester. Experimental and modelling data were then combined to identify the main chemical reactions controlling iron mobility in those anaerobic digesters. Results show that speciation of iron in the sampled anaerobic digesters was controlled by the solid phase through a primary reaction (sulfide precipitation to form pyrite and ferrous sulfide) and secondary reaction (phosphate precipitation to form vivianite). However, iron-sulfide precipitates represented only 10-30% of the total iron in the sampled digesters, while iron-phosphate precipitates represented more than 70%. The significance of the high quantity of vivianite in these digesters is that phosphate-rich anaerobic digesters will be more iron-mobile environments than sulfide-rich digesters, with iron being more readily exchanged between the solid and liquid phases during digestion, implying a higher level of bioavailability and the tendency to interact more readily with organic and inorganic counterparts.